ANALISIS TINGKAT KESALAHAN SISWA KELAS VIII MTs PADA MATERI TEOREMA PHITAGORAS - Ahmad Ahmad; Habib Ratu Perwira Negara; Kiki Riska Ayu Kurniawati; Gilang Primajati (LP2M IAI NURUL HAKIM, 2022)
The purpose of this study was to determine the error rate of class VIII MTs students on the Pythagorean theorem material. The research method used is descriptive quantitative type. The population in this study were all students of class VIII MTs Nurul Yaqin with a total of 21 students. The instrument used in this study used a multiple choice test of 25 items on the Pythagorean theorem material. While the results obtained in this study is the average value of the percentage error rate of 57.81% which includes less criteria (less than 70%). This is due to a lack of understanding of the subject matter of the Pythagorean theorem. In understanding the concept of the Pythagorean theorem, students are required to master the prerequisite material such as integer operations, fraction operations, and planes. If these prerequisite materials have not been mastered, it will be difficult to understand the concept of the Pythagorean theorem.